1985
DOI: 10.1056/nejm198504253121705
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Secretion in Postmenopausal Osteoporosis

Abstract: Calcitonin deficiency has been implicated in the pathogenesis of accelerated bone loss, especially in postmenopausal osteoporosis. To investigate this issue, we studied 25 patients with untreated postmenopausal osteoporosis, 14 age-matched and sex-matched healthy controls (spinal bone mineral density greater than or equal to age-specific and sex-specific mean), and 5 women who had undergone total thyroidectomy. Each subject received an intravenous infusion of 2 mg of elemental calcium per kilogram of body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
3

Year Published

1986
1986
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(29 citation statements)
references
References 15 publications
1
24
1
3
Order By: Relevance
“…A significant correlation between IL-1 and years since menopause was also found in the entire untreated postmenopausal population (r = -0.50; P < 0.005). [8][9][10][11][12][13][14][15] years after menopause were divided into two groups, those whose IL-1 activity was above the upper normal limit (defined as the mean IL-1 activity of the premenopausal women plus 2 SD), and those with normal levels of IL-1. Based on this criterion, a significant difference (P = 0.002) was found between the two groups in the distribution of the nonosteoporotic and the osteoporotic subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant correlation between IL-1 and years since menopause was also found in the entire untreated postmenopausal population (r = -0.50; P < 0.005). [8][9][10][11][12][13][14][15] years after menopause were divided into two groups, those whose IL-1 activity was above the upper normal limit (defined as the mean IL-1 activity of the premenopausal women plus 2 SD), and those with normal levels of IL-1. Based on this criterion, a significant difference (P = 0.002) was found between the two groups in the distribution of the nonosteoporotic and the osteoporotic subjects.…”
Section: Resultsmentioning
confidence: 99%
“…There are no consistent changes in the levels of endocrine resorption stimulators, parathyroid hormone and 1,25-dihydroxyvitamin D3 (9,10), and plasma calcitonin, an inhibitor of resorption, while lower in women than in men (11), is not remarkably diminished in postmenopause (12). These findings have suggested that estrogen may act by modifying the production of one or more of the local factors now known to influence remodeling events.…”
Section: Introductionmentioning
confidence: 99%
“…Group I consisted of five subjects aged [19][20][21][22][23] Statistical analysis. Data were normalized using a log-transformation for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, although pharmacologic amounts of calcitonin prevent bone loss associated with osteoporosis, low circulating calcitonin is not a characteristic of osteoporosis. The opposite is apparently true: excessive skeletal calcium release such as that occurring with osteoporosis apparently stimulates calcitonin secretion and increases the concentration of calcitonin in plasma (Tiegs et al, 1985;McCarroll, 1993). Thus, the finding of decreased serum calcitonin with relatively high dietary zinc probably should not be considered undesirable.…”
Section: Discussionmentioning
confidence: 99%